The Influence of Safety Practices on Construction Labour Productivity. (September 2019) - Setiani, Yulia; Majid, Muhd Zaimi Abd
Abstract: The objective of this study was to identify the most influencing safety practices on construction labour productivity. One hundred and forty four peoples from contractor, client and consultant companies in the construction industry are the respondents of the questionnaire survey. Thirty one safety practices have been selected from various sources as the questionnaire item. The average index method, Kruskal Wallis test, and factor analysis technique were used to make an analysis and get a result. The result showed that the using of basic personal protective equipment (PPE) and the existence of safe guard device are the most influencing safety practices on labour productivity. The contractor result is the highest score compare with the client and consultant. From factor analysis technique, it is obtain five safety practices groups base on their similarities. This study revealed that the implementation of good and appropriate safety practices can give a positive influence to the labour productivity base on middle management staff opinions.